RECONSTRUCTION OF THE CONCEPT OF HUMAN RIGHTS IN ISLAM: A STUDY ACCORDING TO THE THOUGHTS OF SHEIKH YUSUF AL-QARADAWI - Tomi Saputra (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
Sheikh Yusuf al-Qaradawi is an Islamic scholar known for his contributions to the discourse on contemporary issues in Islam. This study aims to analyze Sheikh Yusuf al-Qaradawi's perspective on Human Rights in Islam. The research utilizes a descriptive-analytical method to analyze Sheikh Yusuf al-Qaradawi's works and views related to the concept of Human Rights. The findings indicate that Sheikh Yusuf al-Qaradawi believes that Islam recognizes and guarantees human rights as an integral part of religious teachings. According to his perspective, human rights in Islam encompass fundamental rights such as the right to life, freedom of religion, freedom of expression, the right to justice, and the right to personal security. However, Sheikh Yusuf al-Qaradawi also emphasizes that human rights in Islam should be understood within the context of Islamic law and religious principles. This means that human rights must not contradict Islamic teachings and the moral principles established by Allah. Furthermore, this research reveals that Sheikh Yusuf al-Qaradawi argues that Islam has great potential to protect and promote human rights. In his view, concepts such as justice, equality, and human dignity emphasized in Islamic teachings form the basis for the development of Islamic human rights concepts.